GAFF-IC: realistic viscosities for isocyanate molecules with a GAFF-based force field - Lenzi, Veniero (2019)
Aliphatic diisocyanates and their derivatives are key liquid components in the industrial processing of polyurethane materials. In particular, for the synthesis of crosslinked polyurethane materials, the higher functionality molecules obtained by reacting three -or more- diisocyanates are of interest. However, despite their widespread application, the relation between molecular structure and macroscopic physical properties, in particular viscosity, is poorly understood in these systems. In this work, we introduce a new force field parameter set, GAFF-IC, based on the widely-used and versatile GAFF force field, meant for accurate predictions of physical properties of isocyanate-based molecular liquids. The new parameters allow to predict the vaporization enthalpies and densities of several isocyanate-based molecules, which are found in excellent agreement with the available experimental data. The effectiveness and transferability of the improved parameters is verified by calculating the viscosities of several isocyanates, isocyanate dimers (uretdiones) and isocyanate trimers (isocyanurates), resulting in accurate viscosity predictions in excellent agreement with experimental values.